Pitesamisk grammatik - en jämförande studie med lulesamiska - Sjaggo, Ann-Charlotte (Samisk senters skriftserie, 2015)
The grammar book Pitesaami Grammar, a study in comparison to Lulesaami has been developed in the period 2011-2014 within the project "From coast to coast", which focuses on the encounters, environment and migration within the Pitesaami area on the Norwegian and Swedish sides of the border. The focus of the project has among other things been the comparative study between the Pite- and Lulesaami languages, aiming to produce a descriptive grammar of the Pitesaami, the result of which is this book. The Pitesaami – one of many varieties, or dialects, of the Saami language – is spoken today in the area of Arjeplog by only forty or so speakers. Pitesaami is a threatened language without any officially accepted orthography, but a proposed and well-functioning one exists today, very similar to the Lulesaami orthography and used in this study. The Pitesaami language, as well as Lulesaami, is characterized by consonant gradation. In addition, in inflected and conjugated words, even the vowels change according to specific rules presented in this study. Like other Saami dialects, Pitesaami is rich in forms but also very regular. There are nine personal forms within the verbal paradigm. Three of them, the dual forms (us two, you two, those two), are a rarity among current languages. Nouns, adjectives, pronouns and numerals are inflected into nine different cases. This study explains all these phenomena and clarifies the structure and grammatical rules of the Pite- and Lulesaami. This grammar aims to assist those who want to learn the language and should be regarded as part of a revitalization process. Combined with dictionaries, texts, sound-recordings and living speakers, this grammar will enable you to understand the construction of the language, so you can start practicing both to speak and write it.Good luck with your Saami studies!